Kajian Sosial Ekonomi Masyarakat Lahan Gambut di Kabupaten Tanjung Jabung Timur, Jambi - Surati Surati (Jurnal Ilmu Kehutanan, 2021)
This research aimed to analyze the socio economic and its dynamics of the community in Sidomukti Village, Dendang District, and Pandan Sejahtera Village, Geragai District, Tanjung Jabung Timur Regency, Jambi Province. Respondents were selected purposively based on their farming practices on deep peatlands. Thematic and descriptive analyses were used in this research. The results showed that the majority of the communities of the two villages was Javanese who came to the villages through transmigration programs in the 1980s. Their had insufficient knowledge about peatland utilization because they used to manage mineral soil in their place of origins. Their main jobs were farmers, planters, and laborers with oil palm and areca nut as the main commodities. The average income in Pandan Sejahtera Village was IDR3,832,800/month, greater than in Sidomukti Village which was IDR3,661,850/month. Farmers tended to plant commodities that were currently favored in the market instead of their suitablility with the biophysical conditions of peatlands. Guidance is needed to improve farmers’ knowledge of land management and species selection that have high economic values and market captures as well as are suitable for biophysical properties of deep peatlands and agroforestry techniques.